Implementation of a psychiatric nursing boot camp to improve the empathy and stigma toward psychiatric patients in nursing students - Mahnaz Ghaljeh; Fereshte Ghaljaei; Nasrin Rezaee; Mahin Naderifar; Majid Dastras; Azizollah ArbabiSarjou; Najmeh Ghiamikeshtgar (Journal of Education and Health Promotion)
BACKGROUND: Considering the emphasis of nursing bachelor’s curriculum on teaching practical skills and clinical education, psychiatric nursing education is considered one of the weak points of nursing education. The present study was conducted with the aim of implementation of a psychiatric nursing boot camp to improve the empathy and stigma toward psychiatric patients in nursing students. MATERIALS AND METHOD: The present study is a semiexperimental study with a pretest and post-test group design, which was conducted by census sampling method on 35 nursing students of the 6th semester at Zahedan University of Medical Sciences in 2023. The application of fishbowl technique, simulation, and learning café along with games were used to improve the empathy and stigma of nursing students. Jefferson’s standard empathy questionnaire and kassam stigma were used to collect data. Data analysis was carried out using Statistical Package for the Social Sciences (SPPS) 28.0, Shapiro–wilk test, and paired t-test. A significance level of less than 0.05 was considered. RESULTS: According to the results, 35 nursing students (16 boys and 19 girls) participated in this research. The results showed that the average age of the students was (23.28 ± 2.34) years. The average empathy score of the students was (47.40 ± 3.22) before the intervention and (58.06 ± 2.50) after the intervention. These findings showed that the empathy score was significantly higher after the intervention; P < 0.001. Also, the average stigma score was (62.28 ± 3.37) before the intervention and (54.54 ± 1.30) after the intervention, and the results showed that the average score of this variable was significantly higher after the intervention (P < 0.001). CONCLUSION: This study shows that psychiatric nursing boot camp and training through simulation of auditory hallucinations, learning cafe, and tight fish technique can play a role in increasing students’ empathy and reducing stigma toward psychiatric patients and is a suitable tool in reducing stigma and increasing empathy in nursing students can be incorporated into routine training.